Outcomes of Hereditary Breast-Ovarian Cancer Syndrome: A single center experience - Manzoor Khan, Sameen Bin Naeem, Shazia Asim, Mussadique Ali Jhattial, Neelam Siddiqui (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the survival and progression patterns of Hereditary Breast and Ovarian Cancer (HBOC) at our hospital. Methods: We did retrospective cohort study of thirty patients presenting with hereditary breast ovarian and cancer diagnosed and treated at Shaukat Khanum Memorial Cancer Hospital and Research Center (SKMCH&RC), Lahore, Pakistan from 1994 to 2012. Patient’s demographics, clinical and histopathology data was obtained from cancer registry department of SKMCH&RC hospital. Chi-square test and independent sample T-test were used to analyze the data to find the association between variables i.e. age, comorbidities, BMI and progression free survival. Result: All patients except two received chemotherapy and surgery as per guidelines. Of the thirty patients, thirteen patients had shown progression free survival (PFS) out of which one patient died whereas progression of disease was observed in seventeen patients of HBOC out of which six patients were expired. Comorbidities and family history of cancer did not show statistically significant results for the mortality (P > 0.05). Metastasis and presence of ascites indicated statistically significant influence on PFS having P value < 0.05. CA-125 at presentation, chemotherapy usage and adjuvant therapy did not show significant impact on PFS (P > 0.05). Conclusion: Seven cases of diagnosed HBOC died. We identified that there were 43.33% cases of diagnosed HOBC who met progression free survival and rest developed the progression. Metastasis and presence of ascites showed significant impact for the progression of disease.